Animism: Comparing Durkheim and Chidester"s analyses of EB Tylor"s theory of religion - Strijdom, Johan ca. 21. Jh. (HTS teologiese studies, 2021)
The purpose of this research study was to compare the analyses of the anthropologist Edward Tylor’s animist theory of religion in the work of two major scholars of religion. At the beginning of the 20th century, Durkheim refuted Tylor’s classical explanation of the origin of religion, before he would proceed to develop his own sociological explanation. At the turn of the 21st century, from a postcolonial South African location, David Chidester offered a critical analysis of the triple mediation under colonial and imperial conditions that made Tylor’s evolutionary theory possible. By foregrounding definitions, making arguments explicit and comparing these two assessments, the two analyses shed light on each other as well as allowed us to view the issue of animism in a new light. This article concluded by highlighting points that emerged and need continuing attention in the academic study of religion.Contribution: This article, as part of a collection on re-readings of major theorists of religion, offers a comparison of Durkheim and Chidester’s analyses of Tylor’s classical animist theory of religion. By comparison, the analyses shed light on each other and on the theory of animism itself, highlighting critical issues that deserve the continuing focus of students of religion.